TREATMENT PATTERNS OF NEWLY DIAGNOSED PEDIATRIC ULCERATIVE COLITIS AND CROHN'S DISEASE PATIENTS IN THE IMPROVECARENOW REGISTRY. (21st January 2021) - Hunter, Theresa; Komocsar, Wendy; Colletti, Richard; Liu, Chunyan; Benkov, Keith; Dotson, Jennifer; Steiner, Steven; Zhang, Nanhua; Crandall, Wallace
Abstract: Objectives: The objective of this study was to assess current treatment patterns of pediatric ulcerative colitis (UC) and Crohn's disease (CD) patients, using data in the ImproveCareNow (ICN) registry. Methods: Pediatric (2–17 years) patients in the United States who were newly diagnosed with UC or CD between June 1, 2013-December 31, 2019, who had their first recorded ICN visit within 6 months of diagnosis and who were actively followed for at least 12 months (± 90 days) were included in this study. Descriptive statistics of baseline patient demographics were summarized for the overall IBD patient population and separately for UC and CD. Treatment patterns (including use of corticosteroids, 5-aminosalicylic acid (5-ASA), 6-mercaptopurine/azathioprine (6-MP/AZA), methotrexate, tumor necrosis factor inhibitors (TNFi) [adalimumab, infliximab, certolizumab, golimumab, and their biosimilars], ustekinumab, vedolizumab, and other medications [natalizumab and tofacitinib]) were assessed at the initial baseline visit, and at 1-year and 3-year time points. Results: A total of 6, 504 pediatric IBD patients (UC=1, 784; CD=4, 720) were included in this study. Patients had a mean age at diagnosis of 13.0 years (UC=13.2; CD=12.9), 57.1% were male (UC=49.6%; CD=60.0%), and 81.0% were White (UC=81.2%; CD=81.0%) (Table 1). At the initial ICN visit, 46.4% of UC patients were prescribed a corticosteroid, while 19.8% received a 5-ASA, 12.6% received a TNFi, 10.4% received a 6-MP/AZA, 3.0% received methotrexate, and 0.3% received vedolizumab. At the initial visit, 40.2% of CD patients were prescribed a corticosteroid, while 29.1% received a TNFi, 18.5% received a 6-MP/AZA, 12.4% received methotrexate, and 3.3% received a 5-ASA. At the 1-year and 3-year time points, rates of 5-ASA and corticosteroid use decreased among UC patients; however, rates of 6-MP/AZA, methotrexate, and TNFi increased (Table 2). Similarly, at the 1-year and 3-year time points, rates of corticosteroids among CD patients decreased; however, rates of methotrexate and TNFi increased (Table 2). There was also an increase in use of ustekinumab and vedolizumab over time among UC and CD patients. Conclusion: These results highlight the current treatment patterns of pediatric UC and CD patients in the United States. At the initial ICN visit, the 46% of UC and 40% of CD patients were receiving corticosteroids, however, at 1-year and 3-years after initial visit, over 30% of UC patients and over 60% of CD patients were receiving TNF inhibitors with considerably reduced corticosteroid use.